Quantum Sensing for Energy Applications: Review and Perspective. Issue 8 (15th June 2021) - Crawford, Scott E.; Shugayev, Roman A.; Paudel, Hari P.; Lu, Ping; Syamlal, Madhava; Ohodnicki, Paul R.; Chorpening, Benjamin; Gentry, Randall; Duan, Yuhua
Abstract: On its revolutionary threshold, quantum sensing is creating potentially transformative opportunities to exploit intricate quantum mechanical phenomena in new ways to make ultrasensitive measurements of multiple parameters. Concurrently, growing interest in quantum sensing has created opportunities for its deployment to improve processes pertaining to energy production, distribution, and consumption. Safe and secure utilization of energy is dependent upon addressing challenges related to material stability and function, secure monitoring of infrastructure, and accuracy in detection and measurement. A summary of well‐established and emerging quantum sensing materials and techniques, as well as the corresponding sensing platforms that have been developed for their deployment is provided here. Specifically, the enhancement of existing advanced sensing technologies with quantum methods and materials is focused on, enabling the realization of an unprecedented level of sensitivity, placing an emphasis on relevance to the energy industry. The review concludes with a discussion on high‐value applications of quantum sensing to the energy sector, as well as remaining barriers to sensor deployment. Abstract : Quantum information science is expected to profoundly impact science and engineering fields, and has already found its initial applications in sensing. Current progress towards applying quantum sensors to energy infrastructure and materials, complex energy system processes, advanced manufacturing, and energy system security is summarized. An overview of current challenges in the field and opportunities for future innovations is given as well.